Is obesity associated with taste alterations? a systematic review - Peinado, Beatriz Rodrigues Risuenho; Frazão, Deborah Ribeiro; Bittencourt, Leonardo Oliveira; Souza-Rodrigues, Renata Duarte de; Vidigal, Maria Tereza Campos; da Silva, Douglas Teixeira; Paranhos, Luiz Renato; Magno, Marcela Baraúna; Fagundes, Nathalia Carolina Fernandes; Maia, Lucianne Cople; Lima, Rafael Rodrigues (Frontiers in Endocrinology, 2023)
Background: Obesity is a growing chronic public health problem. The causes of obesity are varied, but food consumption decisions play an important role, especially decisions about what foods to eat and how much to consume. Food consumption decisions are driven, in part, by individual taste perceptions, a fact that can influence eating behavior and, therefore, body mass. Methodology: The searches were conducted in the electronic databases Pubmed, Web of Science, Scopus, Lilacs, and the grey literature (Google Scholar and Open Grey). The acronym PECO will be used, covering studies with adult humans (P) who have obesity (E) compared to adult humans without obesity (C), having as an outcome the presence of taste alterations (O). After searching, duplicates were removed. The articles were first evaluated by title and abstract, following the inclusion and exclusion criteria; then, the papers were read in full. After the studies were selected, two reviewers extracted the data and assessed the individual risk of bias and control statements for possible confounders and bias consideration. The narrative GRADE system performed the methodological quality assessment using the New Castle Ottawa qualifier and analysis of certainty of evidence. Results: A total of 445 records were identified from the database search, of these 20 were considered eligible. Forty percent of the elegible studies show that there was an association between obesity and different taste alterations for different flavors comparing with normal weights adults. In the analysis of the methodological quality of the twenty studies, three showed good quality, four showed fair quality and three showed poor quality. Conclusion: Despite methodological limitations, the results of the studies suggest the existence of a association between obesity and taste alterations, but further investigations with more sensitive methodologies are necessary to confirm this hypothesis.